Physiological Effects and Adaptations of Marathon Running: A Comprehensive Review - Bindas, Jan; Hamouta, Jakub; Doroszuk, Wiktor; Długosz, Patrycja; Jerzak, Marika (Journal of Education, Health and Sport, 2025)
Background. Marathon running is one of the most popular and rapidly expanding forms of endurance exercise. It provides well-documented cardiovascular, metabolic, and musculoskeletal benefits. Understanding the systemic adaptations and potential health risks associated with long-distance running is essential in sports medicine and physiology. Aim. The aim of this review is to summarize current scientific knowledge on the physiological effects of marathon training and participation, focusing on cardiovascular, metabolic, musculoskeletal, renal, respiratory, and immune responses, as well as training strategies and performance-enhancing methods. Material and Methods. This narrative review is based on a comprehensive literature analysis conducted through PubMed from 2018 to 2024. Keywords used included: "marathon", "endurance running", "cardiovascular remodeling", "exercise physiology". Studies involving both professional and amateur marathon runners were considered. Results. Regular marathon training induces numerous systemic adaptations, including increased VO₂max, improved lipid profile, enhanced musculoskeletal efficiency, and neurohormonal regulation. However, acute and chronic health risks such as arrhythmias, renal stress, respiratory fatigue, and musculoskeletal injuries have also been observed. The degree of physiological strain is strongly correlated with training volume, experience, and recovery strategies. Conclusions. Marathon running, when properly managed, promotes global health and physical performance. However, excessive or inadequately supervised training may lead to adverse effects, particularly in less experienced athletes. Individualized approaches to training, screening, and recovery are essential to maximize benefits and minimize risks.